2016
DOI: 10.1016/j.matbio.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metabolic health in mouse models of fibrillin-1 perturbation

Abstract: Mutations in the microfibrillar protein fibrillin-1 or the absence of its binding partner microfibrilassociated glycoprotein (MAGP1) lead to increased TGFβ signaling due to an inability to sequester latent or active forms of TGFβ, respectively. Mouse models of excess TGFβ signaling display increased adiposity and predisposition to type-2 diabetes. It is therefore interesting that individuals with Marfan syndrome, a disease in which fibrillin-1 mutation leads to aberrant TGFβ signaling, typically present with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…To date, no known skeletal diseases have been definitively linked to mutations in the human MAGP-1 gene. The MAGP-1 gene polymorphism rs2284746, discussed above, was associated with increased height in the GIANT consortium database [55], which is in agreement with skeletal studies in mice showing increased bone length in animals lacking MAGP-1 [56]. MAGP-1 deficiency in mice ( Mfap2 −/− ) results in numerous bone defects, supporting a connection between MAGP-1 and skeletal homeostasis.…”
Section: Magp and Clinical Phenotypessupporting
confidence: 66%
See 2 more Smart Citations
“…To date, no known skeletal diseases have been definitively linked to mutations in the human MAGP-1 gene. The MAGP-1 gene polymorphism rs2284746, discussed above, was associated with increased height in the GIANT consortium database [55], which is in agreement with skeletal studies in mice showing increased bone length in animals lacking MAGP-1 [56]. MAGP-1 deficiency in mice ( Mfap2 −/− ) results in numerous bone defects, supporting a connection between MAGP-1 and skeletal homeostasis.…”
Section: Magp and Clinical Phenotypessupporting
confidence: 66%
“…A common trait in MAGP-1-deficient mice is the appearance of lesions on adult animal hind and forelimbs, which were determined to be abnormal healing fractures [13]. These bone lesions, along with increased overall body length, persisted in the MAGP-1-deficient animals through several back-crosses into inbred and outbred mouse strains [56, 57]. The prevalence of bone fractures suggested that bone strength and overall bone quality were compromised in the MAGP-1-deficient background.…”
Section: Magp and Clinical Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…MFAP2 (also known as MAGP-1) binds strongly to fibrillin microfibrils ( 63 , 77 ) and was found to interact directly with both TGF-β and BMP-7 ( 78 ). Disrupting this interaction in mice leads to a marked increase in TGF-β signaling attributed to the loss of its sequestration into the fibrillin microfibril network ( 79 ). As such, MFAP2 plays a key role in modulating fibrillin-growth factor signaling.…”
Section: Resultsmentioning
confidence: 99%
“…KEGG pathway analysis of MAGP1 co-expressed genes further showed an enrichment of focal adhesion, PI3K-AKT signaling and TGF-β signaling. Previous studies showed MAGP1 was involved in several phenotypic abnormalities of the ECM by regulating TGF-β activity, not impact structural features of ECM (29). And Fibrillin-1 can indirectly mediate TGF-β pathway by binding MAGP1, which tethered the active form of TGF-β to the microfibril (30).…”
Section: Discussionmentioning
confidence: 99%